Active agents, passive principals: does high-powered CEO compensation really improve incentives? - Dow, James (2022)
In this paper we use agency theory to study the active role of the CEO in the formulation of corporate strategy. We allow the agent (CEO) to play a role in defining the parameters of the agency problem, in an incomplete contracting model in which the agent can be rewarded based only on financial performance. Contracts can be renegotiated depending on the proposed strategy. We argue that CEOs will have an incentive to propose difficult, ambitious strategies for change. The principal (the shareholders) can mitigate this by pre-committing to pay high compensation regardless of the manager’s chosen strategy, and will prefer to do so in times of change. In a less changeable environment, they will prefer to wait and see what strategy is chosen before setting compensation. In some circumstances, they will also prefer, if possible, to pre-commit never to pay high compensation.